Leadership Behaviour Models of Kiai Islamic Boarding Schools in the 4.0 Industrial Revolution Era - Farhanudin Sholeh (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2021)
This study aims to describe the leadership behaviour model of Islamic boarding school Kiai in the industrial revolution 4.0 era at Assunniyyah Islamic Boarding School Kencong Jember and Miftahul Ulum Islamic Boarding School Banyuputih Kidul Lumajang. The type of research used is descriptive qualitative related to the leadership behaviour of the Kiai. The data analysis procedure is carried out continuously, simultaneously with data collection and then continued after data collection is carried out. The results of this study are 1). The similarities between the two pesantren are that the Kiai as caregivers both maintain the Islamic boarding school as a noble heritage from the founders of the pesantren, while 2). There are differences in leadership patterns. Pondok Pesantren Assunniyyah Kencong Jember radically separates salaf education from within the pesantren and modern education outside the pesantren. Meanwhile, at Miftahul Ulum Islamic Boarding School Banyuputih Kidul Lumajang, salaf and modern education are within the pesantren environment while still prioritizing salaf education.